The cross-sectional area of the vagus nerve is not reduced in Parkinson's disease patients - Laura C.J. Sijben; Werner H. Mess; Uwe Walter; A. Miranda L. Janssen; Mark L. Kuijf; Mayke Oosterloo; Wim E.J.. Weber; Marcus L.F. Janssen (eNeurologicalSci, 2022)
Background: Recent studies have revealed the importance of the gut brain axis in the development of Parkinson's disease (PD). It has also been suggested that the cross-sectional area (CSA) of the vagus nerve can be used in the diagnosis of PD. Here, we hypothesize that the CSA of the vagus nerve is decreased in PD patients compared to control participants. Methods: In this study we measured the CSA of the vagus nerve on both sides in 31 patients with PD and 51 healthy controls at the level of the common carotid artery using high-resolution ultrasound. Results: The mean CSA of the left vagus nerve in the PD and the control group was respectively 2.10 and 1.90 and of the right respectively 2.54 and 2.24 mm2. There is no difference in CSA of the vagus nerve in PD patients compared to controls (p = .079). The mean CSA of the right vagus nerve was significantly larger than the left (p < .001). Age, sex and autonomic symptoms were no significant predictors of the CSA of the vagus nerve. Conclusion: These findings show that the CSA of the vagus nerve using ultrasonography is not a reliable diagnostic tool in the diagnosis of PD.